Effects Of 10,000 Steps Walking Program In Cardiorespiratory Endurance Of Obese Adolescent - William Jakatama; Sri Wahyudati (Indonesian Journal of Physical Medicine & Rehabilitation, 2017)
Background: Sedentary life style lead to obesity which related into deterioration of cardiac function, anddeconditioning on musculoskeletal system, particularly on walking function. Walking is an important activityin human life, that automatically repeated in daily activity. Doing exercise by walking activity is a simple andsafe exercise. However, in walking exercise prescription, we need to establish what is the objective to achieve.The ten thousand steps of Walking Program (10,000 SWP) is pedometer-based walking program begin in Japanfor adult and elderly, thus the effects in obesity adolescent remains unclear. The aimed of this study was to findthe effect of 10,000 SWP in Cardiorespiratory Endurance (CE) on obese adolescent.Methods:This study was pre and post randomly experimental design with control, in 24 high school obeseadolescent. Subjects divided into two groups, the intervention group that received 10,000 steps walking program5 days in a week for 6 weeks, and the control group that number of step walking recorded by a pedometerwithout daily target. The cardiorespiratory endurance (VO2 max) was evaluated by the six minute walking test(6MWT), that measured before and after intervention.Results: The Intervention and control groups each contain 12 obese high school students, that equal in age,body mass index, and the mean number of walking steps per day. There was no differences between VO2max1 (12.45 ml/Kg ) and VO2max 2 (12.38 ml/Kg ) (p=0.852) in control group, while there was the differencesbetween VO2max 1 (12.44 ml/kg) and VO2max 2 (17.06 ml/kg) (p=0.002) in treatment group.Conclusion: The 10,000 SWP has proven increasing the Cardiorespiratory Endurance of Obese Adolescent.Keywords: 10,000 Steps Walking Program, 6 Minute Walking Test, Cardiorespiratory Endurance, Obese Adolescent.